2021
DOI: 10.1136/bmjspcare-2020-002861
|View full text |Cite
|
Sign up to set email alerts
|

Video hospice consultation in COVID-19: professional and patient evaluations

Abstract: BackgroundProviding care for our patients during the COVID-19 pandemic required a rapid shift to video consultations (VCs). A service evaluation was performed to capture hospice professionals’ (HPs) and patients’ experiences of VC.MethodsOnline or postal surveys were sent to HPs and patients, who had participated in VC between March and July 2020, focusing on their experience and satisfaction with the service.Results31 responses from HPs were received. 19 (61.3%) rated their experience of VC as good, despite 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 4 publications
(3 reference statements)
1
24
0
Order By: Relevance
“…Technical issues have been shown to be problematic in the delivery of VC 12. While the majority of patients surveyed felt they could use their devices easily for VC (70%), consistent with previous studies,11 21 50% of the patients studied required assistance to participate with VC. A proportion of these patients described this assistance as being potentially onerous on their carers, ‘(I) couldn’t use it without my family and they are burdened enough’.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Technical issues have been shown to be problematic in the delivery of VC 12. While the majority of patients surveyed felt they could use their devices easily for VC (70%), consistent with previous studies,11 21 50% of the patients studied required assistance to participate with VC. A proportion of these patients described this assistance as being potentially onerous on their carers, ‘(I) couldn’t use it without my family and they are burdened enough’.…”
Section: Discussionsupporting
confidence: 80%
“…In advance of the COVID-19 pandemic, there was increasing interest in the role of VCs in palliative care service provision, particularly in the delivery of community palliative care (CPC) services 4–8. Telehealth, including VCs, has gained particular prominence in the setting of the COVID-19 pandemic facilitating the safe delivery of clinical care 9–12. It is anticipated that VC will form an integral component of CPC service provision into the future 13…”
Section: Introductionmentioning
confidence: 99%
“… 45 , 46 Experiences reported in evaluations in other clinical services during the pandemic are valuable and promising. 47 49…”
Section: Discussionmentioning
confidence: 99%
“…Philip et al (2022) found that compared with using audio alone, the use of both audio and visual media tools was associated with greater ease of use, satisfaction, and likelihood of future telehealth use for both patients and HCPs. On the other hand, one study described HCPs showing a preference for telephone communication due to a lack of proper equipment and a fear of using video (Milne et al, 2021).…”
Section: Visual Cuesmentioning
confidence: 99%
“…The inclusion of family members in telehealth consultation was viewed positively by both patients and HCPs (Milne et al, 2021).…”
Section: Family Engagementmentioning
confidence: 99%